Impact of light on anoxic/oxic reactors performance, quorum sensing, and metagenomic characteristics - Fei, Xuening (Water science and technology : a journal of the International Association on Water Pollution Research, 2021)
The effect of light has raised attention on wastewater treatment. However, little research has concentrated on the influences of light on activated sludge. In this study, the influences of light on the performance, quorum sensing (QS) and metagenomic characteristics of anoxic/oxic reactors were investigated. The reactor without light (AO1) showed higher total nitrogen (TN) removal (79.15 ± 1.69%) than the reactor with light (AO2) (74.54 ± 1.30%), and significant differences were observed. It was observed that light facilitated the production of protein-like and tryptophan-like substances by employing parallel factor analysis for extracellular polymeric substance (EPS), resulting in more EPS production in AO2, indicating light was beneficial to EPS production. The concentrations of N-acyl-homoserine lactones (AHLs) were various in the two reactors, so the AHLs-mediated QS behaviors in both reactors were also different. These results revealed that light significantly influenced nitrogen removal, EPS, and QS. Metagenomic analysis based on Tax4Fun demonstrated that light reduced the denitrification, stimulated the polysaccharide and protein biosynthesis pathways and down-regulated the AHLs synthesis pathway, resulting in lower TN removal, more EPS production, and lower AHLs concentrations. Based on the above, the likely mechanism was proposed for the influences of light on the reactor